Development of Image Processing & Thermal Camera for Railway Vehicle Bearing Inspection: A Review - Hanifar Kahira; F Ferryanto; Satrio Wicaksono (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2024)
Inspection of the train’s bearings is an important aspect of maintaining the performance and operational safety of the rail transportation system. Bearings act as components that support wheel rotation and transmit loads between the wheels and the axles. The poor condition of bearings can cause operational disruptions, decreased efficiency, and even failures that can endanger the safety of train passengers and personnel. In recent years, the use of thermal camera sensor technology in the inspection of railway bearings has grown rapidly. The thermal camera sensor enables accurate temperature detection and visualization of heat patterns on the bearing surface. Abnormal heating patterns can indicate a problem such as excess friction, wear, or overheating that needs action. In this review paper, the importance of checking bearings on trains, image processing, and object detection technologies in detecting damage, the use of thermal camera sensors in inspections, and the benefits that can be obtained by implementing this technology will be discussed in detail. This study is intended to provide a better understanding of bearing inspection on trains and its contribution to improving the safety and efficiency of the rail transportation system.